Roles of Different Radiations in Treatment of Breast Cancer: Radiations in Treatment of Breast Cancer - Jameel, Usba; Janan Orakzai, Zubair; Rashid, Shamoona; Noureen, Sumaira (Pakistan Journal of Health Sciences, 2022)
The review aimed to describe the role of radiations in treatment of breast cancer. The review also describe that which type of radiation is used to treat different stages of breast cancer i.e, metastatic stage, advance stage and early stage of breast cancer. The radiation therapy plays a significant role in the treatment of breast cancer. The treatment delivery methods are considerably changed in the recent decades. The concept of using radiotherapy for the treatment of breast cancer has remained equally important for oncologists throughout the years still research has been going on to make these radiotherapy sessions more and more convenient for the patients. The combination of breast conservation surgery an APBI can result in survival without having any other health related issues for other nearby organs. Recent findings have reported about incorporation of APBI into clinical usage. APBI should be used for patients with low risk of ductal carcinoma or in case of first stage of invasive ductal cancer which has prominent margins for the excision, and where the estrogen receptor positivity is clear. Radiation therapy is effectively used for the treatment and management of loco regionally advanced and distant metastatic disease. There is research going on to find most appropriate technique in which convenient and protected procedure is used for patients to avoid any side effects. New and advanced techniques are used to limit radiation related toxicity.